Environmental Disclosures and Size of Selected Indian Firms - Sahore, Nidhi Sharma; Verma, Anshul (European Scientific Journal, ESJ, 2017)
Business responsibility is an easily said but hard to assume construct of sustainability literature. Out of the nine principles of Business Responsibility Reporting (BRR), the sixth principle envisages the environmental concerns of the businesses. The objective of this study is to explain the response of corporate entities towards Environmental Concerns (EC). The environmental concern of an organization has been gauged through environmental disclosures by these firms under the sixth principle of BRR. The general lack of emphasis on environmental disclosures still remains to be a key challenge to encourage Indian corporate houses to develop and adopt clean technologies, energy efficiency and renewable energy initiatives. The role of clean technologies/environmental technologies is pivotal in ensuring adequate environmental disclosures. But the moot point is, do the firms of certain size would disclose more on EC. There is plenty of literature which suffices the relationship of size and environmental disclosure but by appearing green (disclosures) an organization cannot be green. An organization will be green through its clean technology and energy initiatives. There is a major shift in the sustainability literature by focusing on prevention rather than damaging and curing later. Clean energy initiatives are the first steps to towards preventing/minimizing the environmental damage. Therefore, the next important question arises what explains the variation in clean energy initiatives in an organization. Is it the size of the firm or regulation which leads to disclosing environmental concern (EC.?) The relationship between size of the firm and environmental disclosures related to EC has been found to be significant by applying‘t’ test in the selected sample of 40 companies, while the variation in clean technology initiatives in the same sample has been measured using binary logistic regression. Out of the two independent variables i.e. size and environmental concern it is established that instead of size it is the regulation which significantly pushes companies towards clean technologies and energy initiatives.